Regional financial performance and human development index: Study in Central Java and South Kalimantan provinces - Suranta, Sri; Bandi, Bandi; Perdana, Halim Dedy; Syafiqurrahman, Muhammad (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2019)
The purpose of this study is to find out: (1) the difference Human Development Index (HDI) between Central Java Province and South Kalimantan Province, and (2) the effect of the financial performance of the Regional Government on HDI. The samples of this study were the city and regency in the Provinces of Central Java and South Kalimantan. This study found that there were differences in the level of people’s prosperity as reflected by HDI between Central Java and South Kalimantan. Other finding showed that the financial performance of the Regional Government affected the level of people’s prosperity as measured by HDI.